Is there financial accelerator in indonesian banking? - Dadang Lesmana; Felisitas Defung; Wirasmi Wardhani (University of Merdeka Malang, 2022)
The purpose of this study is to examine the effect of the business cycle on price-cost margins in Indonesian banking. The research method used is the System Generalized Method Moment (SYS-GMM) to analyze 94 conventional banks in Indonesia for the period 2011-2020. The results of this study indicate that the business cycle has two effects on the price-cost margin in Indonesian banking. First, GDP has no effect on the price-cost margin. Second, credit has a negative effect on price-cost margins in Indonesian banks. Our result study is to prove the results of research on